Shame and respectability : a narrative inquiry into Cape Town’s ‘coloured’ families through photographs, cultural practices and oral histories (c. 1950 to 2016) - O’Connell, Siona (University of Pretoria, 2020)
Thesis (PhD)--University of Pretoria, 2018.